Pengembangan Media Pembelajaran Interaktif pada Mata Pelajaran Dasar Listrik dan Elektronika - Rani Zuwe; Elfizon Elfizon (Jurnal Pendidikan Teknik Elektro, 2021)
This research studies producing interactive learning media that is valid and practical in the subject of electricity and electronics in class X TITL in Vocational High School 1 Padang. The type of research used is research and development with ADDIE development model. Interactive learning media developed was used software Construct 2 and validated by 3 validators. Interactive learning media tested limited to class X electric power installation techniques in Vocational High School 1 Padang. Based on the result of the study, interactive learning media validity testing obtained by 0,83 with a valid category. The teacher practicality test result obtained 89,55% with a practical category and the result of the practicality test by student amounted to 85,66% with a practical category. This research has produced interactive learning media that is valid and practical in the basic electricity and electronics subject in basic competence analyzing the theorem of the direct current electric circuit in class X TITL in Vocational High School 1 Padang.